2013
DOI: 10.1007/s12237-012-9584-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Stable Isotope Ratios in Oysters (Crassostrea gigas) and Primary Producers Along an Estuarine Gradient (Bay of Brest, France)

Abstract: Nerot, et al.. Spatial variability of stable isotope ratios in oysters (Crassostrea gigas) and primary producers along an estuarine gradient (Bay of Brest, France). AbstractThis study aimed at characterizing the diet of the oyster Crassostrea gigas along an estuarine gradient in the Bay of Brest (France), through stable isotope (δ 13 C and δ 15 N) measurements in primary producers and wild oysters. The contribution of different potential food sources to the diet of C. gigas was estimated at high spatial resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…The value of d 13 C has been applied to describe how regional differences in the environment include potential foods (Marchais et al 2013;Antonio et al 2010). In the case of Siganus fuscescens, sexual maturation occurs at a body size greater than 170 mm (Katayama et al 2009), and whereas body size differed between the two sites, the majority of our samples was at a younger stage with a body length less than 170 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The value of d 13 C has been applied to describe how regional differences in the environment include potential foods (Marchais et al 2013;Antonio et al 2010). In the case of Siganus fuscescens, sexual maturation occurs at a body size greater than 170 mm (Katayama et al 2009), and whereas body size differed between the two sites, the majority of our samples was at a younger stage with a body length less than 170 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Field investigations of the impact of extensive cultivated C. gigas on chlorophyll concentrations in Wallapa Bay, USA, supported modelled scenarios and showed that although oyster filtration rates were lower than laboratory measurements, the oysters can exert top-down control on phytoplankton production within estuaries (Wheat and Ruesink 2013). Yet isotopic analysis on the diet of wild Pacific oysters on rocky shores along an estuarine gradient in the Bay of Brest (Marchais et al 2013) found that benthic biofilms and resuspended macro algal detritus, rather than phytoplankton, constituted the greatest proportion of the diet. The 1 m height difference between oysters cultivated on trestles and benthic wild oysters may explain variance in the proportion of benthic v pelagic sources (Marchais et al 2013), so caution is necessary at extrapolating impacts of aquaculture to the issue of wild settlement.…”
Section: Impacts On Species Diversity and Ecosystem Functioningmentioning
confidence: 99%
“…Yet isotopic analysis on the diet of wild Pacific oysters on rocky shores along an estuarine gradient in the Bay of Brest (Marchais et al 2013) found that benthic biofilms and resuspended macro algal detritus, rather than phytoplankton, constituted the greatest proportion of the diet. The 1 m height difference between oysters cultivated on trestles and benthic wild oysters may explain variance in the proportion of benthic v pelagic sources (Marchais et al 2013), so caution is necessary at extrapolating impacts of aquaculture to the issue of wild settlement. A higher near-bed turbulence caused by the roughness of Pacific oyster reefs, together with the high water filtration capacity of the oysters, may increase food intake rate (Troost et al 2009;Troost 2010).…”
Section: Impacts On Species Diversity and Ecosystem Functioningmentioning
confidence: 99%
“…Consequently, the use of stable isotopes is currently the most popular one to address the origin of organic matter in coastal ecosystems (e.g. Darnaude et al, 2004;Banaru et al, 2007;Connolly et al, 2009;Marchais et al, 2013).…”
Section: Introductionmentioning
confidence: 99%